Interpretation and application of international standards on auditing - Collings, Steve (Chichester, West Sussex : Wiley, 2011)
'This book eliminates the complexities contained within the International Standards on Auditing and gets to the heart of what it is that auditing standards want from auditors. Offering practical guidance on how these often difficult to interpret standards are applied to actual practice, the author addresses all the ISAs as reissued as part of the 2018'clarity project,' giving illustrative examples of how they are used in real life. The book also covers the regulatory framework of auditing and provides a summary of the five ethical standards as mapped by the IAASB. An ideal resource for auditors and financial accountants.'--
'This book strips out the complexities contained within International Standards on Auditing and gets to the heart of what it is that auditing standards want from auditors'--
Keywords: Auditing -- Standards; Financial statements -- Standards